Aggregation behavior and antimicrobial activity of a micellar system of binary ionic liquids - Shah, M.U.H. (Elsevier B.V., 2018)
Ionic liquid (IL) surfactants have attracted great attention as potential alternatives to conventional surfactants because of their unique tailor-made physicochemical properties. However, in most cases, the aggregations formed by single IL surfactants in aqueous media are unstable, even when using a large amount of surfactant. To address this limitation, here we investigated the aggregation behavior of binary IL surfactant micelles composed of the ILs choline oleate (ChoOl) and choline laurate (ChoLau) in aqueous media using tensiometry and dynamic light scattering measurements. Micellar and interfacial parameters including critical micelle concentration (cmc), micellar interaction parameters (Î²), activity coefficients (f1 and f2), surface excess concentration (Ðmax), minimum surface area per molecule (Amin), and the size of surfactant aggregates were studied. In addition, various thermodynamic parameters such as the Gibbs free energy of micellization (âGo mic), standard Gibbs free energy of adsorption (âGo ad), molar free energy (Gmin), and the excess Gibbs free energy of micellization (ÎGex) were also evaluated. A non-ideal synergistic interaction was observed for the mixed IL surfactant system, which formed larger micelles (105â120 nm) compared with those formed with a single IL (86â102 nm). The formed micelles were found to be thermodynamically stable with regards to all the mole ratio of ILs system. The antimicrobial activity of the single as well of the mixed IL system against Gram-positive and -negative bacteria displayed a low toxicity profile that fell in the range of âpractically harmlessâ (100â1000 mg Lâ1). The results suggested that the micellar system composed of mixed IL surfactants provides unique physical, chemical, and biological properties may offer novel opportunities for various applications such as oil dispersants. Â© 2018 Elsevier B.V.